Media Political Communication: Textual Analysis Of News Coverage On The Development Of Mining Areas In Raja Ampat (Coverage On Tempo Online And Media Indonesia) - Afina Ruqayyah (Fakultas Ilmu Komunikasi Universitas Bhayangkara Jakarta Raya, 2025)
ABSTRACT In his book